PERAN SOSIAL WANITA, ANTARA YANG MENGEKANG DAN MEMBEBASKAN - Arief Suryadinata, Abdul Hakim (EGALITA, 2011)
The position of women in society is often regarded as second-class, making the backward condition and used as scapegoats for the backwardness of a society and nation. And even worse, the treatment of women by putting it as second-class communities are often mentioned as religious injunctions of Islam. On the other hand, there are those who want to empower women by giving women the freedom to freely, by demanding their equality with men in all aspects, without considering the differences that have been given by God to men and women. So what happens is the increasing number of family breakdown leading to divorce and loss of sosial community building. Hencethe need for reconstruction of a fair idea about the position of women, both on the relationship of women with men, as well as the position and role of women in family and society. Based on observations of the hadiths of the Messenger of Allah, it was shown that a Muslim woman at the time (shahabiyah) has had a very complex role in the community. Nevertheless, they do not leave their primary role in the family and still uphold the ethicsof religion in the publik domain.